Perancangan Sistem Pemesanan Bucket dan Hampers Berbasis Web Openchart Pada UMKM di Padang - Ilahi, Iklas; Wandira, Raju; Haqqi, Ikhlasul (Yayasan Lembaga Studi Makwa, 2023)
Micro, Small, and Medium Enterprises (UMKM) in Padang, West Sumatra, have a significant contribution to the regional economy, especially in the production of buckets and hampers that are highly sought after for events such as weddings, birthdays, and other major occasions. However, the manual ordering system still in use often causes inefficiencies, recording errors, and limited marketing reach. To address various forms of these problems, this research aims to design an web-based ordering system that can improve the operational efficiency of SMEs and provide convenience for customers.This research uses the Research and Development (R&D) method with stages of needs analysis, system design in the form of development, testing, and system evaluation. Data was collected through interviews, observations, and literature studies to understand the needs of SMEs and customers. This design is carried out using the web platform, which is an open-source e-commerce system, thus allowing flexibility in feature development. Testing involves end users to ensure the system meets operational needs.The results of this study show that the web-based ordering system can improve the efficiency of the ordering process, reduce the risk of administrative errors, and expand the marketing reach of SMEs. This system also provides a better user experience through the ease of online ordering. In conclusion, the implementation of this system helps SMEs in Padang become more competitive and relevant in the continuously evolving digital era.